Analisis Pelanggaran Hak Pada Manusia Yang Dilakukan Oleh Organisasi Yang Ada Di Papua - Faturohman Faturohman; Franc Dieqo Sinaga; Filan Tropi Hulu (Lembaga Pengembangan Kinerja Dosen, 2024)
The implementation of human rights in Papua has been a matter of national and international concern for several decades. This prolonged conflict can involve various factors, including government organizations. Violations of this right can be carried out by other organizations in Papua and can have an impact on the local community. Papua has a long history of conflict, armed conflict between the army and separatist groups such as the Papuan Organization which has caused various violations of rights. Not only that, there are also various military operations that can be carried out to control the security situation, which often results in accusations of serious violations of rights. Many efforts were involved in solving this case, namely by using torture and other violence. The existence of this case certainly has various impacts, one of which is that these violations have resulted in psychological trauma, insecurity, and also a decline in the quality of life of the people in Papua. In addition, distrust of the government and security agencies is increasing, exacerbating conflict situations and can also hamper the peace process.